1996
DOI: 10.1161/01.res.79.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Acute Reductions in Blood Flow and Shear Stress Induce Platelet-Derived Growth Factor-A Expression in Baboon Prosthetic Grafts

Abstract: Abrupt reductions in fluid shear stress induce subendothelial smooth muscle cells (SMCs) to proliferate in experimental prosthetic grafts. Platelet-derived growth factor (PDGF), an important SMC mitogen, is expressed by cultured endothelial cells and modulated by shear stress. We hypothesized that this growth factor would be modulated by changes in shear stress in vivo. Bilateral aortoiliac prosthetic grafts were implanted into five baboons. High flow was generated by construction of femoral arteriovenous fist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 61 publications
2
66
0
2
Order By: Relevance
“…These studies showed that reduced blood flow upregulated the PDGF gene, whereas increased blood flow exerted an opposite effect in nonhuman primate polymer vascular grafts. 26,33 These results clearly demonstrated that blood flow played a role in the regulation of mitogen expression in blood vessels.…”
Section: Influence Of Eddy Blood Flow On At 1 Receptor Expressionmentioning
confidence: 63%
See 2 more Smart Citations
“…These studies showed that reduced blood flow upregulated the PDGF gene, whereas increased blood flow exerted an opposite effect in nonhuman primate polymer vascular grafts. 26,33 These results clearly demonstrated that blood flow played a role in the regulation of mitogen expression in blood vessels.…”
Section: Influence Of Eddy Blood Flow On At 1 Receptor Expressionmentioning
confidence: 63%
“…For instance, lowered fluid shear stress, with reference to physiological blood shear stress, promoted SMC proliferation and intimal hyperplasia, whereas increased fluid shear stress prevented these evens in experimental polymer vascular grafts in nonhuman primates. 26,32,33 Investigations on human and animal arterial atherosclerosis have supported these observations. [1][2][3][4] However, how oscillatory, low, fluid shear stress and increased shear stress gradients differentially regulate vein graft remodeling remains to be investigated.…”
Section: Discussion Eddy Flow and Focal Intimal Hyperplasiamentioning
confidence: 82%
See 1 more Smart Citation
“…Baboons have been used to study effects of hemodynamics and antithrombotic therapy on neointima development in AVGs (27,28) and to evaluate bioengineered grafts (29). However, baboon purchase and care is expensive, and there is significant public opposition to the use of nonhuman primates in research.…”
Section: Animal Models Of Av Accessmentioning
confidence: 99%
“…High sheer stress has been associated with vascular dilatation through inhibition of smooth muscle cell proliferation and high levels of nitric oxide release, whereas low sheer stress has been associated with smooth muscle cell proliferation and lack of vasodilatation [120][121][122][123] . Poor hemodynamic profiles could be a risk factor for neointimal hyperplasia development and poor venous dilatation, and the degree of luminal stenosis is dependent upon both the magnitude of neointimal hyperplasia and the capacity for vasodilatation or vasocontriction.…”
Section: Hemodynamic and Vascular Remodeling In Hemodialysis Access Dmentioning
confidence: 99%